Analysis of Added Value in Banana Chips Agro-Industry (Case Study of UMKM Nuri Rashi in Padang City) - Fiana, Risa Meutia; Aulia Raihan, Sukma; Santosa, Santosa (Institute of Research And Community Service, Andalas University / LPPM Universitas Andalas, 2024)
The study focuses on the analysis of the added value of bananas into bananas chips on the UMKM Nuri Rashi Banana chips in Padang City. The high banana production in Western Sumatra has the potential to increase the value of bananas in banana chips. Analysis of the value added used in this study is using the Hayami method. The value added analysis found that the processing of bananas into bananas chips on UMKM Nuri Rashi's banana chips has a value added of Rp 25.587 it can be understood that the added value of each kilogram of banana fruit that is processed into bananan chips is Rs 25.587, and yields a high value added ratio of 121.8%. The high rate of value added from processing bananas to bananas chip indicates that this processing is worthy to be developed.